Laparoscopic Versus Conventional Surgery for Colotomy Closure; Molecular Evaluation - Hameed Abed Kate (Journal of Global Pharma Technology, 2016)
The goal of this study was to compare between laparoscopic and conventional surgery on the healing of colotomy closure by using cruciate mattress suture pattern. Twelve adult local breed bucks (male goat), were used, it was divided into two equal groups. In group A (Conventional group), the colotomy incision was created and closed by cruciate mattress suture pattern, while in group B (Laparoscopic group), the colotomy closure by same pattern intracorporeally using 3-0 Polygalactin-910.Molecular assessment at zero time, one and three weeks post operation by vascular endothelial growth factor (VEGF) and fibroblast growth factor-2 (FGF-2) gene expression to evaluate the colotomy healing process.Molecular evaluations indicate that the highest value of vascular endothelial growth factor was noted in group A whereas the lower value in group B at one-week post operation. The highest value of fibroblast growth factor-2 was noted in group B while the lower value in group A at one-week post operation. In conclusion the study clearly demonstrated that the healing process in cruciate suture laparoscopically superior to that occur in conventional technique.Keywords:Enterotomy, Colotomy, Laparoscopy, Cruciate Mattress Suture Pattern, Molecular, VEGF, FGF-2, Quantitative PCR, Colon, Bucks. Goat.